Taxonomic status of Euphylliidae corals in Peninsular Malaysia based on morphological structures and phylogenetic analyses using Mitochondrial COI Gene1 - Khodzori, Mohd. Fikri Akmal; Saad, Shahbudin; Nordin, Noor Faizul Hadry; Ku Sulong, Ku Abdullah Ulwan; Mat Zain, Khairul Amira (Pleiades Publishing, Ltd., 2017)
The morphological and molecular studies provide greater taxonomic resolution for the scleractinian coral identification. The Euphylliidae corals are among the scleractinian family for which their corallite and polyp morphologies have been examined for species identification. However, knowledge on the molecular study for coral identification in Malaysia is very limited. Therefore, this study aimed to examine the morphological structures and phylogenetic analyses for six Euphylliidae coral species using the mitochondrial gene of cytochrome oxidase subunit I (COI). The results showed that the Euphylliidae corals are present under both “complex” and “robust” coral clades as supported by many researchers. The result also revealed that the species phylogeny of Euphylliidae corals is in concordances with its morphological structures of corallites. It can be concluded the combination between morphological structures and phylogenetic analyses provide more accurate identification than relying on morphological study alone. Hence, it provides a future direction for the scleractinian research progress in species identification.